2023
DOI: 10.1007/s11248-023-00343-z
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship and food consumption of immatures and adults of Apis mellifera and Scaptotrigona bipunctata exposed to genetically modified eucalyptus pollen

Abstract: Eucalyptus comprises the largest planted area of cultivated production forest in Brazil. Genetic modification (GM) of eucalyptus can provide additional characteristics for increasing productivity and protecting wood yield, as well as potentially altering fiber for a diversity of industrial uses. However, prior to releasing a new GM plant, risk assessments studies with non-target organisms must be undertaken. Bees are prominent biological models since they play an important role in varied ecosystems, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The invitro safety study that examined allergenicity, toxicity, digestibility, and heat lability of the NPTII and CP4-EPSPS proteins was described previously (Avisar et al, 2023;Fuchs et al, 1993;Harrison et al, 1996). Additionally, bee safety studies were conducted, as outlined by Santos et al (2023). These studies collectively demonstrated that there are no safety risks associated with the NPTII and CP4-EPSPS proteins to humans, animals, or the environment.…”
Section: Safety Assessmentsmentioning
confidence: 99%
“…The invitro safety study that examined allergenicity, toxicity, digestibility, and heat lability of the NPTII and CP4-EPSPS proteins was described previously (Avisar et al, 2023;Fuchs et al, 1993;Harrison et al, 1996). Additionally, bee safety studies were conducted, as outlined by Santos et al (2023). These studies collectively demonstrated that there are no safety risks associated with the NPTII and CP4-EPSPS proteins to humans, animals, or the environment.…”
Section: Safety Assessmentsmentioning
confidence: 99%
“…22 Field studies over three years demonstrated that cultivation of the event had no adverse effects on non-target organisms including arthropods and soil microbiota, and a study evaluating the effects of 751K032 and non-GM FGN-K pollen on the bee species Apis mellifera and Scaptotrigona bipunctata larvae and adults, found no differences in mortality and survival rates. 23 Moreover, the CP4-EPSPS and NPTII proteins were heat-labile, readily digestible, and according to the bioinformatics analyses, are unlikely to elicit allergenic reactions. Both the CP4-EPSPS protein 24 and 25 and the NPTII protein 26 are safe for human and animal consumption and exposure to the environment.…”
Section: Introductionmentioning
confidence: 99%